In search of opportunities? The barriers to more efficient internal labor mobility in Ukraine - Johannes Koettl; Olga Kupets; Anna Olefir; Indhira Santos (IZA Journal of Labor & Development, 2014)
Ukraine's economy lacks dynamism, and this is both the cause and the effect of people not moving across the regions. The rate at which Ukrainians move from one region to another within the country is only half of what would be expected in comparison with other countries. This paper examines the barriers that prevent workers from moving within Ukraine, using information from focus group discussions and expert surveys. It also offers recommendations for creating greater labor mobility in Ukraine through addressing institutional bottlenecks and defines five key areas for improvement, including the population registry system, housing and credit markets, vocational education and training systems, labor market institutions, and the social welfare system.
Keywords: J61; J68; P25; 330; Internal labor mobility; Housing market; Barriers to migration; Transition economies